The impact of stack parameters on the temperature difference of a thermoacoustic cooler - Mohd Saat, Fatimah Al Zahrah; Rosle, Nur Damia Asma; Abd. Rahim, Irfan; Raja Osman, Raja Nor Firdaus Kashfi (Vinča Institute of Nuclear Sciences, Belgrade, Serbia, 2022)
Thermoacoustics offer alternative solution for cooling needs where a method that is safer to environment is used. The thermodynamic process that needs to be completed by using interaction between inert gaseous and porous material must be made efficient so that the system works properly. This paper reports numerical and experimental investigations of the use of several porous material in air at atmospheric pressure to provide cooling effect. Experimental investigation was also conducted by using cheap and abundant materials as the porous media. Results were collected at two different frequencies and with two different stack lengths. The study showed that thin-walled honeycomb porous structure made of polycarbonate offers the best temperature for thermoacoustic cooler with air at atmospheric pressure. The best COP of 4.73 was recorded. Disparity between numerical and experimental results is expected to be the result of losses that need to be carefully addressed in the future especially when long stack is used in the system.